800 meter aerobic power maintenance - Astrand, P. O.
Training for the 800 meter run must develop the energy systems used during the performance of this specific racing distance. Astrand (1:304) has determined that a two minute maximal effort depends 50% on aerobic and 50% on anaerobic sources of energy. Faster 500 meter efforts depend even more on anaerobic sources. Both energy systems must be developed and strengthened by 800 meter training. However, it is my contention that many 800 meter runners neglect their aerobic power levels by doing mainly anaerobic training (quality speed work) during the competitive-racing season. This oversight may have limiting effect upon 800 meter performance.